Analysis of The Improvement of Students’ Critical Thinking Skills and Scientific Literacy Through The Development of Ethnoscience-Based PJBL E-Modules in Science Learning: A Systematic Literature Review - Muhamad Hendri Diarta; Dini Sudianti; Gisna Haerani (Indonesian Publication Center, 2026)
This study analyzes the effectiveness of integrating ethnoscience, local wisdom, and e-modules based on Project-Based Learning (PjBL) to improve students' critical thinking skills and scientific literacy. This research is highly urgent due to the limited comprehensive synthesis regarding the integration of these three specific components in modern 21st-century science education. The method used is a literature review of 20 relevant scientific articles. The synthesis results clearly show that this integration contributes significantly to learning outcomes. Ethnoscience effectively bridges modern science with local knowledge to make learning contextual. The PjBL model trains higher-order thinking skills through investigation and projects. Meanwhile, e-modules successfully strengthen independent learning interactively and flexibly. The synergy of these three components is proven to increase student engagement, understanding, analysis, and evaluation. However, success remains influenced by teacher readiness, resource availability, and student autonomy. This study provides a vital theoretical contribution toward relevant science learning innovations for the future.